Statistical system in ancient Egypt - Muhammad Ghanem Hammoud (Journal of College of Education, 2025)
This study, titled "The Statistical System in Ancient Egypt," aims to shed light on the significant development of the administrative system adopted by the royal authority in the statistical system to assess resources, impose taxes, and organize human and economic activities. Statistics were an essential part of the central government's administration and were directly linked to the temple and the king. Their purpose was to estimate land, count the population, livestock, and economic assets, ensuring the continuity of the financial system and political and societal stability. The ancient Egyptian economy was organized with accurate records, through which the Egyptians were able to organize a complex agricultural society, plan their resources, control taxes, and direct labor to ensure the continuity of the state and its central system
Keywords: Statistics; inventories; census; taxes; Nile.